17β-Estradiol Accelerated Renal Tubule Regeneration in Male Rats After Ischemia/Reperfusion-Induced Acute Kidney Injury. Issue 2 (August 2016) - Wu, Chia-Chun; Chang, Chia-Yu; Chang, Sheng-Tsung; Chen, Sheng-Hsien
Abstract : ABSTRACT: Ischemic/reperfusion injury (IRI) is the most common cause of acute kidney injury (AKI). Murine studies report that pretreatment with 17β-estradiol protects against AKI using multiple mechanisms, but how 17β-estradiol is involved in regenerating tubular cells is unknown. To visualize the kidney injury and repair, we used 17β-estradiol to treat rats with postischemic acute kidney injury. AKI was induced by clamping the renal pedicle for 90 minutes 2 weeks after a unilateral nephrectomy. Rats were treated with an intravenous injection of 17β-estradiol or vehicle immediately after reperfusion. Kidney injury was assessed by measuring biochemical and histopathological changes. Immunohistochemical staining of vimentin, proliferating cell nuclear antigen (PCNA), and E-cadherin were used to assess dedifferentiation, proliferation, and redifferentiation. Rats treated with 17β-estradiol had less kidney injury than did vehicle-treated rats post-IRI day 1. The number of PCNA-positive (PCNA Pos ) cells was significantly higher in post-IRI kidneys on day 1 in 17β-estradiol-treated rats. Moreover, vimentin Pos and E-cadherin Pos cells, which were interpreted as regeneration markers, were expressed earlier and significantly more copiously in 17β-estradiol-treated rats. We hypothesize that 17β-estradiol attenuates IRI-induced AKI by reducing inflammation and accelerating injured tubular cell regeneration.